2021
DOI: 10.3390/molecules26113459
|View full text |Cite
|
Sign up to set email alerts
|

Bisindole Alkaloids from the Alstonia Species: Recent Isolation, Bioactivity, Biosynthesis, and Synthesis

Abstract: Bisindoles are structurally complex dimers and are intriguing targets for partial and total synthesis. They exhibit stronger biological activity than their corresponding monomeric units. Alkaloids, including those containing C-19 methyl-substitution in their monomeric units, their synthetic derivatives, and their mismatched pairs can be attractive targets for synthesis and may unlock better drug targets. We herein discuss the isolation of bisindoles from various Alstonia species, their bioactivity, putative bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 98 publications
(298 reference statements)
0
7
0
Order By: Relevance
“…As a result of this surge, numerous methods have been devised for the production of naturally occurring BIMs and their functionalized analogues (see Scheme 1 ). 7 , 11 , 33 , 34 Interestingly, most methods utilize 3-indole aromatic alcohols to afford symmetrical and unsymmetrical 3,3′-BIMs using a condensation strategy with appropriate nucleophiles. 19 , 35 In addition, the most common reaction protocols used in the synthesis include expensive and excess amounts of catalysts such as Cu-catalysts, 36 TsOH, Ga(OTf) 3 , Zn(OTf) 2 , etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this surge, numerous methods have been devised for the production of naturally occurring BIMs and their functionalized analogues (see Scheme 1 ). 7 , 11 , 33 , 34 Interestingly, most methods utilize 3-indole aromatic alcohols to afford symmetrical and unsymmetrical 3,3′-BIMs using a condensation strategy with appropriate nucleophiles. 19 , 35 In addition, the most common reaction protocols used in the synthesis include expensive and excess amounts of catalysts such as Cu-catalysts, 36 TsOH, Ga(OTf) 3 , Zn(OTf) 2 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this surge, numerous methods have been devised for the production of naturally occurring BIMs and their functionalized analogues (see Scheme ). ,,, Interestingly, most methods utilize 3-indole aromatic alcohols to afford symmetrical and unsymmetrical 3,3′-BIMs using a condensation strategy with appropriate nucleophiles. , In addition, the most common reaction protocols used in the synthesis include expensive and excess amounts of catalysts such as Cu-catalysts, TsOH, Ga­(OTf) 3 , Zn­(OTf) 2 , etc. Several catalytic pathways were also developed to afford BIMs, which includes Bronsted or Lewis acid, methanol, iodine, electrolysis methods, metal salts, visible light, and enzymes. Moreover, solid acidic catalysts such as Amberlyst, montmorillonite clay K-10, TiO 2 , ZrOCl 2 /SiO 2 , HClO 4 –SiO 2 , and P 2 O 5 /SiO 2 have also been investigated so far. Over the last decades, methods for fabricating symmetrical and unsymmetrical 2,3′- and 3,3′-BIMs have primarily focused on the indolylation of 3-indolylmethyl alcohol, sulfone, malononitrile, 2,4,6-trimethoxybenzene, etc. with indole derivatives. Although the divulged methodologies are phenomenal, they have some downsides, such as the need for expensive and higher catalytic loading, harsh reaction conditions, time-consuming reaction procedures, use of hazardous organic solvents, inadequate yields, and a constrained substrate scope.…”
Section: Introductionmentioning
confidence: 99%
“…C 20 -vakognavine diterpenoid alkaloids have been shown to exert noticeable anti-inflammatory activity nearly equal to aspirin; thus, they may be a potential aspirin alternative [42,43]. Angustilongines have shown strong anticancer cytotoxicity against various human cancer cell lines with excellent IC 50 values ranging from 0.02 to 9.0 µM [44,45].…”
Section: Marine-derived Alkaloidsmentioning
confidence: 99%
“…Bisindole alkaloids are a class of star molecules in indole compounds. Since the isolation of a bis(indolyl)imidazole topsentin and its analogs from Topsentia genitrix more than a decade ago [ 13 ], scientists have successively isolated various novel bisindole alkaloids from marine organisms as well as from microorganisms; they found that these alkaloids had powerful and diverse biological activities, including antiviral, antitumor, antibacterial and anti-inflammatory activities [ 14 ]. Their unique and concise structures and broad biological activities make them an important leading skeleton in the creation of new drugs.…”
Section: Introductionmentioning
confidence: 99%